PENGARUH STATUS SOSIAL EKONOMI RUMAH TANGGA DAN LITERASI EKONOMI TERHADAP PERILAKU KONSUMTIF SISWA - Nurul Lailiya; Sunanik Sunanik (Jurnal Pendidikan Ekonomi, 2019)
The purpose of this study was (1) to determine the effect of household socioeconomic status on students' consumptive behavior, (2) to determine the effect of economic literacy on students' consumptive  behavior,  (3)  to  determine  the  effect  of  household  socioeconomic  status  and economic  literacy  on  students'  consumptive  behavior.  This  research  method  is  quantitative research. The sample in this study were 74 students of X students of SMAN 1 Kampak. The technique used in data collection uses a questionnaire to obtain data on household socioeconomic status (X1) and consumptive behavior (Y), while the test is to obtain data on students' economic literacy values (X2). The results of this study indicate that (1) there is a significant influence between  household  socioeconomic  status  on  student  consumptive  behavior,  (2)  there  is  a significant influence between economic literacy on students' consumptive behavior, (3) there is a significant influence between household socioeconomic status and literacy economics on student consumptive behavior.